1994
DOI: 10.1007/bf00185771
|View full text |Cite
|
Sign up to set email alerts
|

Development of the spinal nerves in the mouse with special reference to innervation of the axial musculature

Abstract: Development of the mouse spinal nerves was studied. On E11 (11th day of gestation), the primitive spinal nerve fascicle extended ventrally in the anterior half of the sclerotome. Spinal nerves in the forelimb region united with each other to form the primitive brachial plexus. Their terminal segment was covered by a peculiar cell mass. On E12, five primary branches developed along the primitive spinal nerve trunk. The ramus dorsalis was originally a cutaneous nerve, supplying two series of branches to the skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…11E,F); in an adult opossum (and in mammals in general) there is no connection from C3 to the brachial plexus (Harris, 1939) (verified for M. domestica by our laboratory, data not shown). In mouse, C3 never grows towards or into the brachial plexus during embryonic development (Nakao and Ishizawa, 1994). Thus, although the anterior expansion of the forelimb bud seems to have impacted early spinal nerve growth into the limb, this is corrected as development proceeds so that in the adult a typical mammalian pattern is observed.…”
Section: Spinal Nerve Migration Into the Heterotopic Forelimb Budmentioning
confidence: 99%
See 1 more Smart Citation
“…11E,F); in an adult opossum (and in mammals in general) there is no connection from C3 to the brachial plexus (Harris, 1939) (verified for M. domestica by our laboratory, data not shown). In mouse, C3 never grows towards or into the brachial plexus during embryonic development (Nakao and Ishizawa, 1994). Thus, although the anterior expansion of the forelimb bud seems to have impacted early spinal nerve growth into the limb, this is corrected as development proceeds so that in the adult a typical mammalian pattern is observed.…”
Section: Spinal Nerve Migration Into the Heterotopic Forelimb Budmentioning
confidence: 99%
“…By stage 31, the branch from C3 into the brachial plexus is greatly diminished (F, arrow). In mouse, C3 never grows towards the brachial plexus (Nakao and Ishizawa, 1994). nt, neural tube; np, nasal pit; t, tongue muscle precursors; fl, forelimb bud; s, somite; an, accessory nerve; hn, hypoglossal nerve.…”
Section: Research Articlementioning
confidence: 99%
“…We found that EphA3 is expressed in motor neurons starting at E10 of mouse embryogenesis, during which time motor axons extend into the periphery and begin to make pathway choices (32). In view of the limb bud expression of ephrin A ligands (3,14,16,33), and our own demonstration that ectopic EphA3 expression can direct retinal axon guidance decisions (2), we hypothesized that EphA3 directs axon guidance decisions in the MMC.…”
mentioning
confidence: 99%
“…Namely, a phylogenetically constant ramification pattern reflects muscle phylogeny. This seems to be supported by the fact that the primary and secondary branches of the intercostal nerves are at least differentiated during its development, and that the route of the secondary nerves are more unstable than that of the primary (Nakao & Ishizawa, 1994.…”
Section: ) Implication Of Constant Ramification Patterns In Muscle Pmentioning
confidence: 98%